High‐Performance Supercapacitor Applications of NiO‐Nanoparticle‐Decorated Millimeter‐Long Vertically Aligned Carbon Nanotube Arrays via an Effective Supercritical CO2‐Assisted Method. (9th November 2015) - Cheng, Junye; Zhao, Bin; Zhang, Wenkang; Shi, Feng; Zheng, Guangping; Zhang, Deqing; Yang, Junhe
Abstract : Nickel oxide (NiO) nanoparticles are distributed uniformly in the vertically aligned carbon nanotube arrays (VACNTs) with millimeter thickness by an effective supercritical carbon dioxide‐assisted method. The as‐prepared VACNT/NiO hybrid structures are used as electrodes without binders and conducting additives for supercapacitor applications. Due to the synergetic effects of NiO and VACNTs with nanoporous structures and parallel 1D conductive paths for electrons, the supercapacitors exhibit a high capacitance of 1088.44 F g −1 . Furthermore, an asymmetric supercapacitor is assembled using the as‐synthesized VACNTs/NiO hybrids as the positive electrode and the VACNTs as the negative electrode. Remarkably, the energy density of the asymmetric supercapacitor is as high as 90.9 Wh kg −1 at 3.2 kW kg −1 and the maximum power density reaches 25.6 kW kg −1 at 24.9 Wh kg −1, which are superior to those of the NiO or VACNTs‐based asymmetric supercapacitors. More importantly, the asymmetric supercapacitors exhibit capacitance retention of 87.1% after 2000 cycles at 5 A g −1 . The work provides a novel approach in decorating highly dense and long VACNTs with active materials, which are promising electrodes for supercapacitors with ultrahigh power density and energy density. Abstract : An effective supercritical CO2 ‐assisted approach is presented for synthesizing vertically aligned carbon nanotube (VACNT)/NiO hybrid structures. NiO nanoparticles are distributed uniformly in the highly dense, millimeter‐long VACNTs. The unique hybrid structures of VACNT/NiO exhibit high capacity and long cycle stability. The great electrochemical properties of the VACNT/NiO hybrid materials plus their simple fabrication make this class of materials attractive for supercapacitor applications.